Assess the Long-term Effect of the Epley Maneuver for Treatment of Benign Paroxysmal Positional Vertigo - علوني, فايز; ابراهيم, مصطفى; داود, روزالين (Latakia University Journal -Medical Sciences Series, 2020)
Introduction: Benign paroxysmal positional vertigo (BPPV) is the most common peripheral cause of vertigo. It can be defined as transient vertigo induced by rapid change in head position, associated with a characteristic paroxysmal positional nystagmus. Posterior canal benign paroxysmal positional vertigo is the most frequent form of BPPV. Patients and methods: A total of 50 patients between 27 and 76 years of age who were diagnosed with unilateral posterior canal into BPPV by using Dix-Hallpike maneuver. Epely maneuver was utilized as treatment. Patients were followed weekly. Cure weeks were recorded. The patients were followed for 12 months for recurrence. Results: The recovery rates at the first, second and third week controls were 78%, 96% and 100%. 10 patients (20%) had recurrence. Conclusions: Adopt the epley maneuver as a treatment for BPPV because it is safe, non-invasive and effective.